2021
DOI: 10.1002/adfm.202104732
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Oriented Metal–Organic Frameworks Assemblies for Water‐Evaporation Induced Electricity Generation

Abstract: Advances in metal–organic frameworks (MOFs) are stimulating interest in water‐evaporation induced electricity generation. Establishing design principles for desirable MOFs and revealing the structure‐activity relationship is essential to development of this field. Around this key issue, herein the concept of “hierarchical oriented MOFs” is proposed and the Cu(BDC‐OH) MOFs are organized into hierarchical oriented assemblies by successively using methods of hydrolysis, anion exchange reaction, and heteroepitaxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
(36 reference statements)
0
29
1
Order By: Relevance
“…(C) Construction process of hydrovoltaic device based on layered Cu (BDC‐OH) MOFs. [ 74 ] Copyright 2021, Wiley‐VCH. (D) The synthetic process of Cu‐BTC nanorod arrays.…”
Section: Selection Of Materials For Harvesting Energy From Water Evap...mentioning
confidence: 99%
See 2 more Smart Citations
“…(C) Construction process of hydrovoltaic device based on layered Cu (BDC‐OH) MOFs. [ 74 ] Copyright 2021, Wiley‐VCH. (D) The synthetic process of Cu‐BTC nanorod arrays.…”
Section: Selection Of Materials For Harvesting Energy From Water Evap...mentioning
confidence: 99%
“…These results indicated that MOFs, 1D porous nanomaterials with a certain density of surface charge, had an “aggregation effect” through layered directional treatment, which could play an important role in evaporation‐driven electricity generation. [ 74 ] However, degradation of MOFs usually occurs on surfaces with defects or no functional groups, causing instability in water. [ 76 ] As shown in Figure 7D, Li et al designed a hybrid membrane, which combined MOFs (Cu‐BTC complex nanorod arrays) with polyaniline (PANI) conductive polymers to improve the stability of MOFs.…”
Section: Selection Of Materials For Harvesting Energy From Water Evap...mentioning
confidence: 99%
See 1 more Smart Citation
“…The water‐evaporation‐induced electricity generates accompanying the liquid–solid triboelectrification. [ 24 ] Inspired by this work, researchers improved the performance of the generator by optimizing its materials, [ 25 , 26 , 27 ] structure, [ 28 , 29 , 30 , 31 ] fabrication process [ 32 , 33 , 34 ] or their combinations. [ 2 , 35 , 36 ] The excellent water‐evaporation electricity nanogenerators have significantly improved its key performance indicators such as open‐circuit voltages (<2 V), short‐circuit current (<1 µA).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the freshwater scarcity, energy is also a big challenge to humanity due to its high demand and limited sources. , Over the past few years, significant efforts have been invested in producing energy together with solar steam generation. , For example, the temperature difference between the evaporative surface and bulk water was used to produce thermoelectricity. Also, by exploiting the enthalpy of the vapor, Li et al were able to generate a maximum open-circuit voltage ( V OC ) of 4.15 V and a short-circuit current ( I SC ) of 0.61 A at a solar intensity of 30 sun . Furthermore, using an ion-selective membrane, Zhou and co-workers have obtained a V OC of 84 mV at a solar intensity of 2 sun from the salinity gradient caused by the water evaporation .…”
Section: Introductionmentioning
confidence: 99%